2014
DOI: 10.1016/j.jcs.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of maize bread quality through modification of dough rheological properties by lactic acid bacteria fermentation

Abstract: This work investigated how sourdough fermentation improves maize bread quality. Maize sourdoughs were made by fermenting maize flour with multiple strains starter culture and with Lactobacillus plantarum. Sourdough fermentation of maize dough brought about a 25-26% increase in loaf volume of maize bread. Confocal laser scanning microscopy revealed a cohesive dough structure in the sourdoughs. Larger cells were also observed in maize breads with maize sourdough. Differential scanning calorimetry showed that mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Future research investigating the combined effects of NaCl, HPMC, and ethanol should be conducted to fully optimize zein‐starch breads. It would also be interesting to determine the compatibility of these ingredients with organic acids and lactic acid fermentation as described by Falade and others () and Sly and others ().…”
Section: Resultsmentioning
confidence: 99%
“…Future research investigating the combined effects of NaCl, HPMC, and ethanol should be conducted to fully optimize zein‐starch breads. It would also be interesting to determine the compatibility of these ingredients with organic acids and lactic acid fermentation as described by Falade and others () and Sly and others ().…”
Section: Resultsmentioning
confidence: 99%
“…The significant influences of microorganisms on the microstructure of starch systems have been widely studied. 37,38 On the basis of variations in RS, TA, and MC, we speculate that the activities of fungi and yeast during fermentation lead to the change of microstructure and the increased T′ 22 relaxation time. To interpret the microstructure changes of glutinous rice, a simplified model was established.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…However, till date, most breads produced from other flours have not shown superior quality to that obtained from 100% wheat flour. A few studies have reported comparable viscoelastic property of modified zein to that of gluten (Falade et al, 2014;Lawton, 1992;Schober et al, 2008;Taylor et al, 2016). Zein (maize prolamin) was reported to display viscoelastic properties similar to that of gluten in aqueous dough systems, when heated above its glass transition temperature (Lawton, 1992;Schober et al, 2008).…”
Section: Breadmentioning
confidence: 99%